Cause of death in patients with rheumatoid arthritis with particular reference to azathioprine. Issue 5 (October 1980) - Lewis, P; Hazleman, B L; Hanka, R; Roberts, S
Abstract : Three hundred and eleven patients with classical or definite rheumatoid arthritis were observed over an 11-year period. This group is of particular interest since 214 patients were given cytotoxic therapy, 203 were treated with azathioprine (52 of these also received chlorambucil or cyclophosphamide), and 11 were treated with cyclophosphamide or chlorambucil alone. Forty-six patients died. This is an excess mortality compared with the expected rate for the general population matched with respect to age and sex. The death rate was higher than expected in the age group 45-64 years but lower in those aged 75 years or over. There were more deaths from neoplasia and ischaemic heart disease in the younger age group. One patient died of lymphosarcoma; treatment had been with corticosteroids, gold, and chloroquine. No other tumours of the reticuloendothelial system were recorded, and no patient developed leukaemia.